Physical properties of homogeneous particleboard based on acacia tree and polyurethane adhesive as a resins - M. N. M., Baharuddin; Norazwani, Muhammad Zain; Eida Nadirah, Roslin; Wan Sharuzi, Wan Harun; Zaeime, Sulong@Zakaria (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
The formaldehyde-based adhesives have always been chosen for manufacturer in the making of particleboard because of the cost. However, it has low moisture resistance and high water absorption. At the same time, formaldehyde-based adhesive also produced gaseous emission that can cause cancer and bronchial health. Meanwhile, the high water resistance, low moisture content and healthy to the human body nowadays becomes most important issues in the making of furniture for market. This research was discusses on the ability of Acacia tree as raw material and polyurethane (PU) as an adhesive for making the homogeneous particleboard. The aim of this research isto looking the impact of using different particle sizes from Acacia tree to the physical properties of the end product. This study also focuses on the potential of paraffin wax as a water repellent agent. The testing of physical properties was includes the thickness swelling (TS) testing, moisture content (MC), density and water absorption (WA testing). The size of Acacia particle was varied from xx>2mm and x>4mm. All particleboards produced was achieve the range of medium density according to the Japan Industry Standard (JIS). The results have shown that the value of the density and the particle size was influenced the result especially for the physical properties. From this research it is proved that the PU as a resin and sawdust of acacia tree with some specific size can be a good binder and material for the particle board industries in future. The paraffin wax also showed a great potential as a water repellent agent based on the reduction of water absorption of the particleboard. The particleboard with sizes between 2mm to 4mm proves better results compared to the smaller or bigger sizes of particle.